2021
DOI: 10.1021/acsapm.1c01332
|View full text |Cite
|
Sign up to set email alerts
|

Cellulose Nanofiber Composite Polymeric Materials with Reversible and Movable Cross-links and Evaluation of their Mechanical Properties

Abstract: Improvement in the elasticity and toughness of polymeric materials is an important issue in the fabrication of polymeric materials. However, solving this issue is challenging because of the trade-off between toughness and elasticity. Herein, citric acid-modified cellulose (CAC) was introduced as a filler into movable cross-linked polymeric materials, in which cyclic molecules move along the polymer chain. The resulting CAC/polymer composite materials contained both reversible and movable cross-links. The rever… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 50 publications
0
12
0
Order By: Relevance
“…This can solve the problems encountered in the use of the existing polymers. Adamantane (Ad) and β-CD cyclodextrin (β-CD) molecules are widely used in supramolecular oil flooding due to their unique properties. , Pu et al created a new type of supramolecular copolymer for enhanced oil recovery. They utilized Ad and β-CD in an aqueous solution to achieve self-assembly through host–guest interactions .…”
Section: Introductionmentioning
confidence: 99%
“…This can solve the problems encountered in the use of the existing polymers. Adamantane (Ad) and β-CD cyclodextrin (β-CD) molecules are widely used in supramolecular oil flooding due to their unique properties. , Pu et al created a new type of supramolecular copolymer for enhanced oil recovery. They utilized Ad and β-CD in an aqueous solution to achieve self-assembly through host–guest interactions .…”
Section: Introductionmentioning
confidence: 99%
“…Using the correlation diagram, the differences in the mechanical properties of the elastomers can be compared more clearly. G f / E generally decreases with increasing E . ,,, On the other hand, the plots of DCP(80) deviated from the linear region shown by the other elastomers, indicating that the DCP elastomers had different mechanical properties.…”
Section: Resultsmentioning
confidence: 91%
“…The addition of additives to polymeric materials is another way to enhance G f or E . It has already been reported that the mechanical properties of glassy polymers can be improved by compositing homogeneous and heterogeneous microparticles. Our group achieved improved G f values by using several mixing methods for adding additives. …”
Section: Introductionmentioning
confidence: 84%
“…Holographic techniques have been proposed to generate complex acoustic fields using only a single ultrasonic source as well as to manipulate multiple objects in an independent way along any spatial direction with speeds approaching 10 m/s [ 6 ]. Composite polymer materials, already used in a wide variety of applications such as [ 10 , 11 , 12 , 13 , 14 , 15 , 16 , 17 , 18 ], play a fundamental role in materials science. Among them, photomobile polymers (PMP), which are materials able to convert light energy into mechanical work, represent the ideal platform for the development of a large variety of touchless devices [ 19 , 20 , 21 , 22 , 23 , 24 , 25 , 26 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 34 ].…”
Section: Introductionmentioning
confidence: 99%